The potency of metakaolin as addition material in high strength self-compacting concrete to increase Modulus of Rupture (MOR) in rigid pavement application. Issue 1 (March 2021) - Wibowo, W; Safitri, E; Setyawan, A; Muslih, Y; Mediyanto, A; Setiawan, B; Syaufina, T R
Abstract: This study focused on the modulus of rupture (MOR) for high strength self-compacting concrete (SCC) using varied metakaolin (MK) composition. The MOR significantly contributes to the resilience and mechanical performance of the rigid pavement, and is enhanced by modifying the regular concrete material. In addition, the MK is known to be potentially economical and occurs abundantly as natural resources. Plain concrete beams with dimensions 400 x 100 x 100 mm3, were tested in the laboratory in an effort to measure the MOR from varied MK composition for each specimen or modified concrete type. The result showed the MOR increase is exclusively as a result of additional metakaolin. Also, the newly modified material was proven to offer more advantages when applied as rigid pavement material. Furthermore, the analytical laboratory result showed the optimum MK dosage was estimated at 20% of the binder weight. This subsequently enhances the MOR by 17.28% compared to non-MK concrete.